Genetic Relatedness of Salmonella Serovars Isolated from Catfish (Clarias gariepinus) and Tilapia (Tilapia mossambica) Obtained from Wet Markets and Ponds in Penang, Malaysia - Budiati, Titik; Rusul, Gulam; Wan-Abdullah, Wan Nadiah; Chuah, Li Oon; Ahmad, Rosma; Thong, Kwai Lin (International Association for Food Protection, 2016)
A total of 43 Salmonella enterica isolates belonging to different serovars (Salmonella Albany, Salmonella Agona, Salmonella Corvallis, Salmonella Stanley, Salmonella Typhimurium, Salmonella Mikawasima, and Salmonella Bovis-morbificans) were isolated from catfish (Clarias gariepinus) and tilapia (Tilapia mossambica) obtained from nine wet markets and eight ponds in Penang, Malaysia. Thirteen, 19, and 11 isolates were isolated from 9 of 32 catfish, 14 of 32 tilapia, and 11 of 44 water samples, respectively. Fish reared in ponds were fed chicken offal, spoiled eggs, and commercial fish feed. The genetic relatedness of these Salmonella isolates was determined by random amplified polymorphic DNA PCR (RAPD-PCR) using primer OPC2, repetitive extragenic palindromic PCR (REP-PCR), and pulsed-field gel electrophoresis (PFGE). Composite analysis of the RAPD-PCR, REP-PCR, and PFGE results showed that the Salmonella serovars could be differentiated into six clusters and 15 singletons. RAPD-PCR differentiated the Salmonella isolates into 11 clusters and 10 singletons, while REP-PCR differentiated them into 4 clusters and 1 singleton. PFGE differentiated the Salmonella isolates into seven clusters and seven singletons. The close genetic relationship of Salmonella isolates from catfish or tilapia obtained from different ponds, irrespective of the type of feed given, may be caused by several factors, such as the quality of the water, density of fish, and size of ponds.